Research analysis on inclusive education - Valdés, René; Jiménez, Luis; Jiménez, Felipe (Fundacao Carlos Chagas, 2022)
The purpose of the present article is to show the results of a systematic literature review on inclusive education research. The bibliography produced from 2016 to 2020 in the category of Education in Latin America in Scimago Journal & Country Rank (SJR) was used as the reference. We reviewed 101 empirical articles, which focused on: (1) the methodology of the studies; (2) the definition of inclusion; (3) the main areas of action; (4) the main barriers; and (5) the main challenges. The findings show the prominence of qualitative methodologies, different definitions of inclusion, multiple areas of action, as well as the recognition of neoliberalism as the main barrier to consolidating inclusive schools.
Panorama de la recherche en éducation inclusive
Radiografia da pesquisa sobre educação inclusiva
Keywords: Revisión de literatura; Investigación educativa; Educación inclusiva